Seroprevalence of hepatitis E virus among blood donors in Qatar (2013‐2016). Issue 7 (28th April 2017) - Nasrallah, Gheyath K.; Al Absi, Enas S.; Ghandour, Rula; Ali, Nadima H.; Taleb, Sara; Hedaya, Laila; Ali, Fatima; Huwaidy, Mariam; Husseini, Abdullatif
Abstract : BACKGROUND: Hepatitis E virus (HEV) is an RNA virus transmitted mainly through zoonotic transmission or fecal–oral route. More than 80% of Qatar's population are expatriates, including many coming from hyperendemic countries; thus, it is important to estimate the seroprevalence and to compare between different nationalities. The results can be useful in alerting blood banks to the importance of HEV screening. STUDY DESIGN AND METHODS: Samples from 5854 blood donations provided by Hamad Medical Corporation were tested in the period between June 2013 to June 2016. Samples were tested for the presence of anti‐HEV immunoglobulin (Ig)G and IgM antibodies and viral RNA using real‐time polymerase chain reaction (PCR). Descriptive statistics, bivariate analysis, and multivariate logistic regression were used. RESULTS: Anti‐HEV seroprevalence was 20.7%. A total of 1198 and 38 donations tested positive for IgG and IgM antibodies, respectively. Of the IgM‐positive donations four tested positive by PCR. A significant association was detected between HEV seroprevalence with age and nationality. CONCLUSION: The seroprevalence of anti‐HEV was high in Qatar. Since HEV IgM and RNA were detected, this suggests the possibility of HEV transmission by transfusion. Blood banks in Qatar and the region should consider screening for HEV, especially when transfusion is intended to pregnant women or immunocompromised patients.